PENGARUH PENGALAMAN PKL DAN KONSEP DIRI TERHADAP KESIAPAN KERJA SISWA MPLB DI KECAMATAN JOMBANG MELALUI EMPLOYABILLITY SKILLS - Akila Raissa Febrianti; Fitriana Rahmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Work readiness is a critical aspect for graduates of Vocational High Schools (SMK) to succeed in the workforce. It is influenced by various internal and external factors, including field work experience (PKL), self-perception, and employability skills. This study aims to analyze the impact of PKL experience and self-perception on work readiness among students enrolled in the Office Management and Business Services Specialty Program (MPLB) in Jombang District, using employability skills as an intervention variable. The study employs a quantitative exploratory research design, with a sample of 149 students selected via proportional random sampling. Data were collected through questionnaires and analyzed using path analysis with SPSS 25, along with a Sobel test to examine mediation effects. The research findings indicate that PKL experience and self-concept have a significant positive impact on employability skills. Furthermore, self-concept and employability skills significantly enhance job readiness, whereas PKL experience does not directly affect it. Mediation analysis reveals that employability skills fully mediate the effect of PKL experience on job readiness and partially mediate the effect of self-concept on job readiness. These findings demonstrate that improvements in students' job readiness depend not only on PKL experience but also on strengthening self-concept and developing employability skills